DEVELOPMENT OF TEACHING MATERIALS BASED ON E-MODULE CLASS X INFORMATICS SUBJECTS - Ike Oktavia; Nurna Listya Purnamasari; Isnaini Meilina Wulandari (STKIP PGRI TULUNGAGUNG, 2023)
The era of globalization and technological developments proves that the world has entered the industrial era of 4.0. The existence of this human activity is easier to get information. Not only information, but in the world of education it also makes it easier for teachers and students to carry out teaching and learning activities. State Vocational High School (SMK) 1 Tulungagung still uses teaching materials that are PDF text. With the lack of variety of teaching materials, students feel quickly bored and bored in the learning process. Less attractive teaching materials make students lazy to learn. In addition, it also affects the value of Student Completeness Criteria (KKM). So the development of e-module-based teaching materials can provide student enthusiasm and motivation in the learning process. This research aims to arouse students' enthusiasm for learning by using e-module-based teaching materials that are interactive and facilitate students in learning. This research method is Lee and Owens (2004). This research uses RD (Research and Development) development research, this research produces a product, and tests the effectiveness of the resulting product. In this study, researchers used the Lee and Owens (2004) development model consisting of five stages, namely Assessment, Design, Development, Implementation, and Evaluation. The eligibility results of media experts get a percentage of 100%, material experts get a percentage of 100%, small group trials get a percentage of 97.6%, and large group trials get a percentage of 92.6%. Based on the average results of the four percentage data, the percentage of products is 97.3% and is included in the